Caregiver distress: A mixed methods evaluation of the mental health burden of caring for children with bladder exstrophy - Spencer, Katelyn A.; Ramji, Jaishri; Unadkat, Pooja; Nadeem, Iqra; Lalakia, Parth A.; Shah, Jay; Reddy, Pramod P.; Canning, Douglas A.; Pippi-Salle, Joao; Merguerian, Paul; Kundu, Anjana; Weiss, Dana A.; et al. (Frontiers in Pediatrics, 2022)
Introduction: Caring for children with bladder exstrophy-epispadias complex (BEEC) exacts a long-term emotional toll on caregivers. Previous studies leave a gap in understanding the impact that caring for a child with BEEC has on caregivers in low and middle income countries (LMIC). We hypothesize that families and caregivers experience psychological distress that has long gone unaddressed. Methods: From 2018 to 2020, researchers conducted a multi-method evaluation of caregiver distress with participants recruited as part of the annual International Bladder Exstrophy Collaboration based in Ahmedabad, Gujarat, India. In 2018, pilot data was collected through cognitive interviews. In 2019, researchers conducted structured interviews predicated on themes from the previous year, which subsequently prompted formal mental health screenings in 2020. Caregivers who reported suicidal thoughts were immediately referred for intervention . Results: In 2018, caregivers described the primary source of stigma arose from their village (n=9, 26.5%). Caregivers also identified long-term concerns (n= 18, 52.9%), including future fertility and marital prospects, as sources of anxiety. In 2019, caregivers substantiated preliminary findings with the primary source of anticipated (n=9, 31%) and experienced (n=19, 65.5%) stigma again stemming from their communities. Both groups identified the collaboration as a positive source of support (n=23, 36.5%). In 2020, caregivers stated decreased emotional wellbeing as number of subsequent repairs increased (n=54, 75%, p=0.002). Caregivers of children who underwent initial surgery within 5 years of screening reported higher anxiety (n=46, 63.8%) and this was exacerbated as the number of subsequent repairs increased (p=0.043). Conclusion: Complex, long-term course of care, including additional surgeries, significantly impacts caregiver distress in the LMIC setting. Screening for caregivers of children with complex congenital anomalies, like BEEC, should be an essential element of any comprehensive effort to alleviate the global burden of disease.